2014
DOI: 10.1371/journal.pmed.1001766
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Replacing Smear Microscopy with Xpert MTB/RIF for Diagnosing Tuberculosis in Brazil: A Stepped-Wedge Cluster-Randomized Trial

Abstract: Betina Durovni and colleagues evaluated whether implementation of Xpert MTB/RIF increased the notification rate of laboratory-confirmed pulmonary tuberculosis and reduced the time to tuberculosis treatment initiation in 14 Brazilian primary care laboratories. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
3
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 29 publications
(33 reference statements)
10
114
3
26
Order By: Relevance
“…O cenário de referência da análise de impacto orçamentário foi o ano de 2013, considerado aqui como o ano inicial de aquisição dos equipamentos pelo PNCT a partir da incorporação do Xpert MTB/RIF na rede de serviços de saúde de dois municípios (Rio de Janeiro e Manaus, Amazonas) em um estudo piloto de implantação 11 . Naquele ano, a baciloscopia era o teste de rotina.…”
Section: Cenário De Referênciaunclassified
See 2 more Smart Citations
“…O cenário de referência da análise de impacto orçamentário foi o ano de 2013, considerado aqui como o ano inicial de aquisição dos equipamentos pelo PNCT a partir da incorporação do Xpert MTB/RIF na rede de serviços de saúde de dois municípios (Rio de Janeiro e Manaus, Amazonas) em um estudo piloto de implantação 11 . Naquele ano, a baciloscopia era o teste de rotina.…”
Section: Cenário De Referênciaunclassified
“…Utilizaram-se como parâmetros para os cálculos do impacto orçamentário os critérios do PNCT para a seleção dos municípios: (i) municípios que notificaram mais de 200 casos novos de TB em 2011 e que tinham um laboratório com estrutura física e de biossegurança equivalente à necessária para a realização da baciloscopia; (ii) capitais estaduais que não notificaram mais de 200 casos novos em 2011, mas que são referência para o diagnóstico e tratamento da TB nos seus estados; (iii) municípios onde há presídios ou com população indígena que notificaram pelo menos 50 casos em 2011, critério utilizado pela alta taxa de TB-MDR nos presídios e pela dificuldade do diagnóstico nas populações indígenas; e (iv) Laboratórios Centrais de Saúde Pública, que são coordenadores da rede estadual de laborató-rios e responsáveis pelos treinamentos e controle de qualidade dos exames realizados. Ademais, a nova tecnologia gera um incremento da taxa de notificação de TB em 15% (IC95%: -6%; 37%) que foi incluída no modelo 11 .…”
Section: Cenário De Referênciaunclassified
See 1 more Smart Citation
“…These data would enable us to evaluate the incremental number of transmissions that a novel test might be able to avert, relative to the existing standard of care. A series of recent high-quality studies suggests that, when patients present with symptoms that are highly suggestive of TB in upper-middle income settings (for example, South Africa and Brazil), the probability of empirical diagnosis is reasonably high [8][9][10][11] -but that a large number of people may be presenting to care with a cough without TB ever being considered 8 . Such studies are crucial to understand the likely diagnostic gaps for TB, but unfortunately, very few such analyses have been performed in settings with fewer resources (for example, most of sub-Saharan Africa 73,74 and Southeast Asia) where empirical diagnosis rates (and the capacity to implement novel diagnostic tests) may be much lower.…”
Section: S65mentioning
confidence: 99%
“…Nevertheless, the link between improved diagnostic sensitivity and better TB detection remains uncertain. Studies [8][9][10][11] in different settings have found little or no change in the number of pulmonary TB diagnoses or deaths when comparing sputum smear microscopy and Xpert MTB/RIF, a more sensitive molecular test 12 . This result may reflect high levels of empirical treatment among people who test negative [13][14][15] .…”
mentioning
confidence: 99%